2016
DOI: 10.1111/anti.12256
|View full text |Cite
|
Sign up to set email alerts
|

Working for Inclusion? Conditional Cash Transfers, Rural Women, and the Reproduction of Inequality

Abstract: Throughout the global South, conditional cash transfer programmes (CCTs) are used to promote socially inclusive development. CCTs are widely evaluated for their capacity to build children's human capital. In contrast, this paper aims to hold "social inclusion" to account by elucidating the impacts of Peru's CCT "Juntos" on the poor, rural mothers who are expected to meet programme conditions. Grounded in extensive ethnographic research in households, clinics, schools, and village halls, the paper interrogates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Another possible way to increase participation is to relax conditionality in the program. Relaxing conditionality can increase participation by reducing the burden of complying with conditions (Cookson, 2016, Ma et al, 2017). For example, relaxing conditionality may incentivize children to attend school at least some of the time.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible way to increase participation is to relax conditionality in the program. Relaxing conditionality can increase participation by reducing the burden of complying with conditions (Cookson, 2016, Ma et al, 2017). For example, relaxing conditionality may incentivize children to attend school at least some of the time.…”
Section: Resultsmentioning
confidence: 99%
“…While the urban poor may be gaining better access to citizenship rights (Lo Vuolo, 2013;Rego and Pinzani, 2013;Sugiyama, 2013), the rural poor confront different landscapes and thus cannot be lumped uncritically with their urban counterparts (e.g., Cookson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Yet as researchers have observed elsewhere (Ballard, 2013;Standing, 2011), such regulations are by no means unique to Brazil: they are common to Conditional Cash Transfer programs (CCTs) like PBF, where social welfare for the poor comes with strings attached. On the one hand comes desperately needed income assistance, while on the other comes a host of obligations that must be fulfilled by program recipients (Cookson, 2016;Sener, 2015). Sam Hickey notes that although poverty reduction schemes like CCTs are crucial to reducing hunger, they also seek to induce specific and desired behaviors within poor populations through program conditionalities (2010).…”
Section: Waiting On the Statementioning
confidence: 99%
See 1 more Smart Citation
“…A formidable body of research from fieldwork through longstanding relations in non-metropolitan communities has shown that CCTs, in the nominal interest of women's development, add hours of unpaid labour, increase burdens and responsibilities without access to the stipulated benefits, and reincorporate women within existing or traditional paradigms of patriarchal power (see e.g. Molyneaux 2006;Cookson 2016). Sarah Bradshaw (2008a) argues the links between the negative impacts of SAPs and the 'social adjustment' impositions of CCTs on beneficiaries by which the poor are adversely incorporated into asymmetrical relations regarding their input to the economy: the IFI's SPP thus acts as a foil for a reinvigorated economic growth platform.…”
Section: Literature Reviewmentioning
confidence: 99%